Modelos de predição do coeficiente de sorção no solo de pesticidas não iônicos: diferentes algoritmos de logP e uma abordagem alternativa de logS. - Reis, Ralpho Rinaldo dos (2013)
Collecting data on pesticide effects on the environment and several ecosystems is a slow and costly process. Therefore, significant research efforts have been focused on developing mathematical models to predict physical, chemical or biological properties of environmental interest. The soil sorption coefficient normalized to organic carbon content (Koc) is a physicochemical key parameter used in environmental risk assessments of substances released into the environment. Thus, several logKoc prediction models that use hydrophobic parameter (logP) or the logarithm of water solubility (logS) as descriptor have been reported in the last decades. Mostly, due to the lack of reliable experimental values of logP or logS, algorithms are used to calculate such properties. Despite the availability and easiness to access several algorithms for this purpose, scientific studies do not describe the procedure adopted to choose the algorithm used in quantitative structure-property relationship (QSPR) studies. Furthermore, the strong correlation between logP and logS prevents their application in the same mathematical equation obtained by multiple linear regression method. Since the sorption process of a chemical compound in soil is related both to its water solubility and its water/organic matter partition, it is expected models that are able to combine these two properties will can record more realistic results. This doctoral dissertation consists of two scientific papers. In the first one, a study was carried out to check the influence of choosing logP algorithm on logKoc modeling. Models were constructed to relate logKoc with logP according to different freeware algorithms. All models were assessed based on their statistic qualities and predictive power. The obtained results clearly showed that an arbitrary choice of the algorithm may not result in the best prediction model. On the other hand, a good choice can lead to obtaining simple models with statistic qualities and predictive power comparable to more complex models. The second paper aims at proposing an alternative approach for logKoc modeling, using simple descriptor of solubility, here referred as logarithm of corrected solubility by octanol/water partition (logSP). Thus, models were built with this descriptor and also with logP and logS conventional descriptors, which are isolated or associated with other explicative variables of easy physicochemical interpretation. The obtained models were validated and compared to other models previously published. The results showed that the use of logSP descriptor to replace the conventional ones led to obtaining simple models with statistic qualities and predictive power that are higher than other more complex models already found in literature.